INVESTIGATING STUDENTS’ CHALLENGGES IN WRITING DESCRIPTIVE TEXTS - Sugianto (Sinar Lima, 2025)
The study aimed to assess students' writing skills and identify the challenges they faced in writing descriptive texts. Using a case study approach, the research followed a descriptive qualitative method. The participants were 28 second-year students from MA NW Nabi’ Nubu’. The research employed writing tests and interviews as data collection tools. The findings revealed that the average score of the students was 69.92, indicating that their ability to write descriptive texts was relatively low. Three students (12%) scored below 60, placing them in the